Pengaruh Penghindaran Pajak dan Leverage Terhadap Nilai Perusahaan yang Terdaftar di BEI - Astuti, Ratna Puji; Murwani, Ani Sri; Erdi, Tio Waskito; Tjandra, Ronowati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research describes the results of research that investigates the effect of tax avoidance and leverage on company value in companies listed on the BEI (Indonesian Stock Exchange) using data from 2020 to 2022. Company value is measured using Tobin's Q while tax avoidance is proxied by the Cash Effective Tax Rate (CASH ETR). Using data from 81 companies or 243 observations, selected through the purposive sampling method. The data testing method used is multiple linear regression analysis. Based on the results of the t test on the first hypothesis, the effect of tax avoidance on company value has a significance value of 0,204 > 0,05 and the second hypothesis on the effect of leverage on company value has a significance value of 0,00 < 0,05. The study finds evidence that tax avoidance has no effect on company value, while leverage has an effect on company value. Simultaneously, tax avoidance, and leverage have a significant effect on company value.